The king's speech - Hooper, Tim; Firth, Colin; Rush, Geoffrey; Carter, Helena Bonham (United Kingdom : UK Film Council / Speaking Film Productions Ltd, 2010)
After the death of his father King George V and the scandalous abdication of King Edward VII, Bertie who has suffered from a debilitating speech impediment all his life, is suddenly crowned King George VI of England. With his country on the brink of war and in desperate need of a leader, his wife, Elizabeth, the future Queen Mother, arranges for her husband to see an eccentric speech therapist, Lionel Logue. After a rough start, the two delve into an unorthodox course of treatment and eventually form an unbreakable bond. With the support of Logue, his family, his government and Winston Churchill, the King will overcome his stammer and deliver a radio-address that inspires his people and unites them in battle.
Special features: Commentary by director ; an inspirational story of unlikely friendship (24').
Based on the true story of King George VI, The King's Speech follows the Royal Monarch's quest to find his voice.
Editor, Tariq Anwar ; music, Alexandre Desplat ; director of photography, Danny Cohen.
Colin Firth, Geoffrey Rush, Helena Bonham Carter.
Filmed at Hatfield House, Hertfordshire, UK and filmed on location in London.
LPF: 18
Keywords: George -- VI, -- King of Great Britain, -- 1895-1952 -- Drama; Logue, Lionel, -- 1880-1953 -- Drama; Speech therapist -- Great Britain -- Drama; Biographical films; Historical films